Using TiO2 nanoparticles as a SO2 catalyst in cement mortars. (10th October 2020) - Fernandes, Cristiane N.; Ferreira, Ruan L.S.; Bernardo, Ricardo D.S.; Avelino, Francisco; Bertini, Alexandre A.
Highlights: Mortars with TiO2 incorporation (2.5–10%) were produced. The effect of adding TiO2 on the mortars physical–mechanical properties was evaluated. The incorporation of TiO2 in mortars in the degradation process of SO2 was investigated. The nano-TiO2 decontaminated the samples previously contaminated by the pollutant SO2 . Abstract: Titanium dioxide (TiO2 ) has been used in building materials to produce products that do not require major maintenance and also contribute to improve air quality and extend the life of buildings. Thus, this research evaluated the effects of incorporation of this substance into cement mortars in the process of degradation of sulfur dioxide (SO2 ), one of the largest atmospheric pollutants. Mortars were developed at a weight ratio of 1:3 (cement: sand), incorporating 2.5%, 5%, 7.5% and 10% of TiO2 relative to the cement weight. Mortars were evaluated in their fresh state (consistency and bulk density) and hardened (dry bulk density, water absorption by capillarity, open porosity and flexural and compressive strength). The samples were exposed to an accelerated aging SO2 (pollutant) chamber, then moistened and exposed to ultraviolet radiation. For this exposure of the samples, two Light Emitter Diodes (LEDs) with wavelengths covering the UV-A range were used: UV (380–420 nm) and blue (420–493 nm). Fourier Transform Infrared measurements were also performed in three stages, which were: (1) before contamination, (2) after SO2 contamination and (3) after radiation exposure. The nano TiO2 incorporation in the mortars contributed to the increase in open porosity and favored the increase in dry bulk density of mortars this was due to the filler effect. In addition, there was an increase in both the compressive strength and the flexural strength for mortars with addition, compared with the reference mortar. It can be concluded that the incorporation of TiO2 improved the physical, mechanical and photocatalytic properties, and enabled the decontamination of mortars due to the action of the SO2 pollutant.